Advanced therapeutic strategies in patellar ligament tendinopathy: from etiology to clinical practice. A literature review. - Julia Stachowiak; Julia Sosin; Anna Pilarz; Maria Zwierzchowska; Aleksandra Sojka; Dariusz Salamon; Wojciech Domagała (Quality in Sport)
Introduction: